AN E.A. PROFESSOR PROVES HIS WORTH - Allan, David (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1984)
In the belief that a few prickings of the conscience may never come too late to save the soul even of an administrator, the Journal, in righteous pursuit of its mission, is convinced that in presenting the following moral tale it is doing the right thing. Written as it is from the perspective of one who already dwells "Down-under" (although like others in that part of the world he is apt to assume that he really lives "Up-above"), the tale may be felt to carry all the more moral force. RÉSUMÉ Convaincu que des remords pourront toujours sauver l'âme, même d'un administrateur, le journal, dans la vaillante poursuite de sa mission, croit fermement qu'il est de son devoir de présenter le conte moral qui suit. Reflétant le point de vue de quelqu'un qui est déjà passé de l'autre côté, ce conte n'en a que plus de force morale.